Determinants of funding sources, profitability, size, and firm value: Empirical evidence on companies in Indonesia - Hidayat, Riskin; Wijaya, Adi; Hermuningsih, Sri; Pinjaman, Saizal Bin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study examines how firm size influences the relationship between internal funding sources, particularly liquidity, and external funding sources, i.e., debt, on firm value, emphasizing profitability’s mediating role.Design/Methodology/Approach: This study examines publicly traded manufacturing companies in the consumer products sector that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. A sample of 43 companies and 215 observations was obtained through a targeted sampling approach. The data were analyzed using WarpPLS 7.0 software, which supports mediated regression analysis.Research findings: The findings indicate that while liquidity positively impacts firm value, this impact is statistically insignificant. Conversely, the debt policy significantly enhances firm value. Furthermore, profitability acts as an effective mediator in the relationship between liquidity and debt policy on firm value, with firm size further amplifying the impact of profitability. These results emphasize the crucial role of profitability as a mediating factor and firm size as a moderating factor.Theoretical contribution/Originality: This study is expected to enrich the Agency and Pecking Order theories by clarifying the role of profitability as a mediator in the relationship between debt policy and firm value with the factor of firm size as a moderating relationship between profitability and firm value, as well as providing practical insights for business executives in making strategic decisions related to the management of funding and corporate debt structure.Practitioner/Policy Implications: Indonesian companies, especially those listed on the Indonesia Stock Exchange and involved in consumer products, can use liquidity and debt to improve performance and firm value. This study takes a fresh perspective by directly addressing profitability's mediating effect and company size's moderating influence. This methodology provides deeper insights into funding sources and corporate value.Research limitations/implications: This study has several limitations, including a focus on manufacturing companies in Indonesia and data limited to 2019 to 2023, which may affect the generalizability of the results. In addition, this study only considers debt policy, profitability, and company size. At the same time, other factors such as ownership structure and macroeconomic conditions are not considered, so expanding the coverage of sectors and regions is recommended and using more sophisticated analytical methods for future research.